Lipase-producing Aspergillus niger LP4 Isolated from Banana Plantations: Lipase Production Optimization via Central Composite Design and Environmental Applications - Fatimah S. Al-Khattaf; Amirtha Mani Punitha; Ashraf Atef Hatamleh; Ponnumuthu Nandhakumari (BioResources)
Lipases degrade triglycerides and are used in detergent, biodiesel production, and chemical industries. In this work, lipase-producing fungal strains were enriched. A total of 10 morphologically different fungi were isolated and screened for lipase production. The isolated indigenous Aspergillus niger LP4 utilized a mixture of Calophyllum inophyllum oil cake and coconut oil cake (1:1), showing greater lipase production (127.5 ± 5.5 U/g substrate) than Calophyllum inophyllum oil cake (120.2 ± 3.4 U/g substrate) and coconut oil cake (103 ± 1.8 U/g substrate). A one-variable-at-a-time approach revealed optimum pH at 6.5 (139.2 ± 4.5 U/g substrate), 30 °C (152.4 ± 7.3 U/g substrate), 6% (v/w) inoculums (174.1 ± 5.4 U/g substrate), and 60% moisture content (180.5 ± 3.3 U/g substrate). After screening bioprocess variables by the traditional method, the selected three variables (pH, inoculum concentration, and moisture level) were optimized by the central composite design experiment. The central composite design gave 2.1-fold more lipase production compared to an unoptimized medium. The F-value of the designed model was 12.98, and the p-value was 0.0002. In this model, the terms A, B, C, A2, and C2 were significant model terms. The crude lipase showed exceptional compatibility with detergents, improved wash performance, and released free fatty acids from the wastewater.